The On-Site Volcanic Cave Conservation Museum at the Dak Nong UNESCO Global Geopark - La, The Phuc (Nhà xuất bản: Đại học quốc gia Moscow., 2022)
The Krong No volcanic caves at the Dak Nong UNESCO Global Geopark (Dak Nong UGGp) were discovered in 2007. Between 2017 and the present, they were com prehensively studied and evaluated for heritage value from the perspectives of geology, biology and cultural studies. These primitive, endogenic caves are aracterized by rich and diverse interior formations, representing seven types of geological heritage as lassified by the UNESCO and its GILGES classification system. The applicable types are A (Paleontology), B Geomorphology), C (Paleo-Environment), D (Rock), E (Stra tigraphy), F (Minerals), and I (Tectonics). The cave system’s wildlife is highly diverse and includes a number of newly discovered species endemic to Krong No. Thanks to research and excavation work, many types of archaeological artifacts have been dis covered in the Krong No volcanic caves, including relics of residence, a tool-making site, burial artifacts, a makeshift hunting camp, and some artifacts possibly expressive of religious ritual. All of these are unique, valuable and rare. The various types of heritage discovered in the Krong No volcanic caves constitute the premise of an on-site conservation museum, established to promote heritage of value, teaching and schol arship, as well as community education and recreation. This article introduces a new direction for further research, related to the development of an on-site conservation museum of the volcanic cave heritage in the context of sustainable ocio-economic development